A methodology to investigate the effect of vertical seismic acceleration on the qualitative dynamic behaviors of a natural circulation loop with parallel nuclear-coupled boiling channels. (February 2018) - Lee, Jin Der; Lin, Yuh Ger; Chen, Shao Wen; Pan, Chin
Highlights: Nonlinear model is proposed to discuss the effect of vertical seismic acceleration. The parametric effects on the seismic-induced oscillations are discussed in a NCL. The present methodology could simulate a real vertical seismic wave. Qualitative nonlinear characteristics of seismic-induced oscillations are studied. The seismic-induced oscillations are highly consistent with the resonance effect. Abstract: By adopting the external force method to consider the impact of seismic vibration on the two-phase flow system, this study integrates the nonlinear dynamic model of a nuclear-coupled boiling parallel-channel natural circulation loop (NCL) developed previously by the authors with the external vertical seismic accelerations to investigate the qualitative dynamic behaviors of the seismic-induced oscillations in the NCL. The methodology employed in this study could simulate a real vertical seismic acceleration and address the major nonlinear characteristics of seismic-induced oscillations by the comparisons between the results caused by the real vertical seismic acceleration and the simulated wave. The seismic-induced oscillations are found to be highly consistent with the resonance effect in different natural circulation stable states. The resonance part of the seismic waves would dominate the nonlinear phenomena of the system under vertical seismic accelerations imposed. The vertical seismic motion could cause in-phase mode of oscillation among boiling channels in this NCL system. In addition, some parametric effects on the seismic-induced oscillations are performed in the present NCL system. The natural circulation system with a higher subcooling may trigger a more prominent resonance phenomenon, due to the inherent stability characteristics of the initial states, and thus lead to a more dramatic seismic-induced oscillation in the cases studied.